Comprehensive Transcriptome Profiling of NAFLD- and NASH-Induced Skeletal Muscle Dysfunction - Guo, Mingwei; Xiang, Liping; Yao, Jing; Zhang, Jun; Zhu, Shuangshuang; Wang, Dongmei; Liu, Caizhi; Li, Guoqiang; Wang, Jiawen; Gao, Yuqing; Xie, Cen; Ma, Xinran; et al. (Frontiers in Endocrinology, 2022)
Nonalcoholic fatty liver disease (NAFLD), characterized by extensive triglyceride accumulation in hepatocytes may progress to nonalcoholic steatohepatitis (NASH) with liver fibrosis and inflammation and increase the risk of cirrhosis, cancer, and death. It has been reported that physical exercise is effective in ameliorating NAFLD and NASH, while skeletal muscle dysfunctions including lipid deposition and weakness, are accompanied with NAFLD and NASH. However, the molecular characteristics and alterations in skeletal muscle in the progress of NAFLD and NASH remain unclear. In the present study, we provided comprehensive analysis for the similarity and heterogeneity of quadriceps muscle (QU muscle) in NAFLD and NASH mice models by RNA-sequencing. Importantly, Gene Ontology and KEGG pathway functional enrichment analysis revealed that NAFLD and NASH led to impaired glucose and lipid metabolism and deteriorated functionality in skeletal muscle. Besides, we identified myokines that possibly mediate crosstalk between muscle and other metabolic organs in pathological conditions. Overall, our analysis revealed comprehensive understanding in molecular signature of skeletal muscle in NAFLD and NASH, thus providing basis for physical exercise intervention against liver diseases.